Peningkatan Pengetahuan Keluarga Pasien tentang Mobilisasi Dini Pascaoperasi untuk Mendukung Proses Pemulihan - Almaidah, Indah; Ambarika, Rahmania (Yayasan Inspirasi El Burhani, 2026)
Introduction: Early mobilization after surgery plays a crucial role in accelerating the patient’s recovery process and preventing complications such as deep vein thrombosis, pneumonia, and delayed wound healing. Despite its importance, the knowledge and participation of patients’ families in supporting early mobilization remain low. Family involvement is essential because proper support and motivation can significantly influence the patient’s postoperative recovery process. Objective: This community service activity aimed to improve the knowledge and attitudes of patients’ families regarding early mobilization after surgery at Setio Husodo Hospital, Kisaran. Method: The program was implemented through socialization and educational sessions conducted using interactive lectures, group discussions, demonstrations, and direct practice under the supervision of health workers. A pre-test and post-test design was used to assess changes in participants’ knowledge and attitudes toward early mobilization. Data were analyzed descriptively to identify improvement levels among participants. Result: The results showed a significant improvement in participants’ understanding and awareness. After the intervention, 90% of families were able to explain the benefits, techniques, and proper stages of early mobilization, compared to only 45% before the program. The activity also fostered a more positive attitude among families in motivating patients to move gradually after surgery, while ensuring safety and comfort under professional supervision. Conclusion: Family health education effectively increases knowledge and participation in early mobilization after surgery. The program successfully empowered families to take an active role in supporting postoperative recovery. Therefore, it is recommended that similar family-based education programs be implemented regularly as part of standard postoperative care in hospitals.